The Effect of Celebrity Attraction on Consumer Loyalty through Trust in Skincare Products among Generation Z Women - Andriansyah Andriansyah; Aprizal Haris Sinaga; Mutia Zahara; Syafrizal Helmi Situmorang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the influence of celebrity attractiveness on the loyalty and trust of Generation Z women in Medan City towards skincare products. A quantitative method involving a poll of 130 participants was used to assess the impact of social media and celebrities on trust and brand loyalty. The results suggest that celebrities’ attractiveness has a notable impact on consumer loyalty and trust. The findings emphasize the significance of celebrities’ physical appeal in influencing favorable consumer opinions on skincare products. Moreover, research has shown that consumer trust plays a crucial role in connecting celebrity attraction with consumer loyalty. This implies that marketing tactics utilizing celebrities have the potential to enhance and maintain long-term connections with consumers. This study offers significant data for marketers who use celebrity attractions to improve consumer loyalty in the skincare business.